Measurements of isomeric cross sections for (n,2n) reaction on 140Ce, 142Nd and 144Sm isotopes around 14 MeV - Reyhancan, IA; Bostan, M; Durusoy, A; Elmali, A; Baykal, A; Özbir, Y (PERGAMON-ELSEVIER SCIENCE LTD, 2003)
In this study, activation cross sections were measured for the Ce-140(n,2n)Ce-139m, Nd-142(n,2n) Nd-141m and Sm-144(n,2n)Sm-143m reactions at six different neutron energies from 13.5 and 14.8 MeV. The fast neutrons were produced via the H-3(d, h)He-4 reaction on SAMES T-400 neutron generator. The cyclic activation technique Was used. Induced gamma activities were measured by a high-resolution gamma-ray spectrometer with a high-purity germanium (HpGe) detector. Corrections were made for the effects of gamma-ray attenuation, dead-time and fluctuation of neutron flux. For these reactions, statistical model calculations for which the pre-equilibrium emission effects are taken into consideration ,were also performed between 13.6 and 14.8 MeV energy range. Theoretical excitation functions and experimental results were plotted together with previous works. (C) 2003 Elsevier Science Ltd. All rights. reserved.
Keywords: OPTICAL-MODEL ANALYSIS; SCATTERING; NEUTRONS; NUCLEI; ENERGY; RANGE; SC-45; Nuclear Science & Technology